Using Mixed Method Research to Evaluate of the Learning-Teaching Process Quality in Pre-School Centers Based on ECERS - Farahnaz Nezhad ghafuri (Alzahra University, 2021)
The present study was conducted to evaluate the quality of the learning-teaching process of the pre-school centers based on the International ECERS standard. For this purpose, 24 pre-school centers were selected based on multi-stage sampling from different regions of the county and custodial organizations and their learning-teaching process quality was evaluated. First, data were collected using observation techniques and ECERS interviews. In the next stage, the status of pre-school centers was judged in the levels of quadruple spectrum: "inadequate, low, good and excellent". At the end and after analyzing the findings, operational solutions based on improving the quality of ECERS standard were presented. Based on the findings of this study, the quality of activities related to language education and children's reasoning, the quality of activities and the quality of the structure of pre-school centers in Qeshm was undesirable. Also, the quality of the structure of the course has the lowest average compared to other dimensions studied and is in a "undesirable" situation. Overall, the results of the evaluation showed that the quality of the learning-teaching process of the pre-school centers in Qeshm mean was 2.07 and according to the ECERS range of 1-7 and a qualitative judgment range is at a "low quality" and undesirable level.